Disentangling the complex microbial community of coral reefs using standardized Autonomous Reef Monitoring Structures (ARMS). Issue 15 (1st August 2019) - Pearman, John K.; Aylagas, Eva; Voolstra, Christian R.; Anlauf, Holger; Villalobos, Rodrigo; Carvalho, Susana
Abstract: Autonomous Reef Monitoring Structures (ARMS) have been applied worldwide to describe eukaryotic cryptic reef fauna. Conversely, bacterial communities, which are critical components of coral reef ecosystem functioning, remain largely overlooked. Here we deployed 56 ARMS across the 2, 000‐km spread of the Red Sea to assay biodiversity, composition and inferred underlying functions of coral reef‐associated bacterial communities via 16S rRNA gene sequencing. We found that bacterial community structure and diversity aligned with environmental differences. Indeed, sea surface temperature and macroalgae cover were key in explaining bacterial relative abundance. Importantly, taxonomic and functional alpha diversity decreased under more extreme environmental conditions (e.g., higher temperatures) in the southern Red Sea. This may imply a link between bacterial community diversity and functional capabilities, with implications for conservation management. Our study demonstrates the utility of ARMS to investigate the response of coral reef‐associated bacterial communities to environmental change.